Inability to Access Addiction Treatment Among Street-Involved Youth in a Canadian Setting. (24th August 2014) - Phillips, Mark; DeBeck, Kora; Desjarlais, Timothy; Morrison, Tracey; Feng, Cindy; Kerr, Thomas; Wood, Evan
<x xml:space="preserve">Abstract</x> From Sept 2005 to May 2012, 1015 street-involved youth were enrolled into the At-Risk Youth Study, a prospective cohort of youth aged 14–26 who use illicit drugs in Vancouver, Canada. Data were collected through semiannual interviewer administered questionnaires. Generalized estimating equation logistic regression was used to identify factors independently associated with being unable to access addiction treatment. The enclosed manuscript notes the implications and limitations of this study, as well as possible directions for future research. This study was funded by the US National Institutes of Health (NIH) and Canadian Institutes of Health (CIHR).